Adhesive resin composition for surface protective film and surface protective film
The adhesive resin composition for surface protection films, featuring a crosslinkable polymer and a specific polyisocyanate crosslinking agent, addresses the challenge of easy peeling and reduced contamination, delivering excellent adhesiveness and peelability for curved or moving surfaces.
Patent Information
- Application Number
- JP2021060208
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-03-31
AI Technical Summary
There is a demand for an adhesive composition that easily peels off and minimizes contamination by the adhesive during peeling, particularly for surface protective films applied to curved or moving surfaces.
An adhesive resin composition for surface protection films, comprising a crosslinkable functional group-containing polymer (A) with a glass transition temperature between -75.0°C and 0.0°C, and a crosslinking agent component (B) that includes an aliphatic or alicyclic polyisocyanate with specific molecular weight and isocyanate group ranges, optimized in content and structure to enhance adhesiveness, peelability, and reduce contamination.
The adhesive resin composition achieves excellent adhesiveness and peelability, while significantly reducing contamination by the adhesive during peeling, making it suitable for surface protection films on curved or moving surfaces.
Smart Images

Figure 0007657638000001 
Figure 0007657638000002 
Figure 0007657638000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive resin composition for a surface protective film and a surface protective film. [Background technology]
[0002] In recent years, plastic films, pressure sensitive adhesives, and adhesives have been used in various fields due to their wide range of functions. Under such circumstances, they are increasingly being used in applications that were few in the past, such as curved surfaces and parts with bending movements, in addition to flat plate-like objects. For example, flexible displays and foldable displays are examples of such applications, and demand has been rapidly expanding in recent years. Accordingly, it is expected that the demand for surface protection films that can follow curved surfaces will also increase.
[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition that includes a (meth)acrylic polymer having a hydroxy group and an acid value of 0 mgKOH / g or more and less than 16 mgKOH / g, an alkylene oxide chain-containing (meth)acrylic oligomer having an acid value of 0.1 mgKOH / g or more and 40 mgKOH / g or less, a polyether-modified silicone having a reactive group, a polyisocyanate compound as a crosslinking agent, and an ionic compound. It is disclosed that the pressure-sensitive adhesive composition can provide a surface protection film for optical members that can simultaneously achieve high levels of antistatic properties and low contamination of adherends. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-128636 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is a demand for a pressure-sensitive adhesive composition that can provide a surface protection film that is easier to peel off and causes less contamination by the pressure-sensitive adhesive when peeled off than the technology described in Patent Document 1 and the like.
[0006] The present invention has been made in consideration of the above circumstances, and provides an adhesive resin composition for surface protection films which, when made into a surface protection film, has good application and peelability and has improved contamination caused by the adhesive during peeling. [Means for solving the problem]
[0007] That is, the present invention includes the following aspects. (1) A pressure-sensitive adhesive resin composition for a surface protective film, comprising a crosslinkable functional group-containing polymer (A) and a crosslinking agent component (B), The glass transition temperature Tg of the crosslinkable functional group-containing polymer (A) is −75.0° C. or more and 0.0° C. or less, The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 1,400 or more and 200,000 or less and an average number of isocyanate groups of 2.0 or more and 6.5 or less, The content of the crosslinking agent component (B) relative to 100 parts by mass of the crosslinkable functional group-containing polymer (A) is 0.5 Parts by weight or more and 15.0 parts by weight or less the law of nature, The crosslinkable functional group-containing polymer (A), An acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less, and having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less, or a urethane-based polymer (A2) having a glass transition temperature Tg of −75.0° C. or higher and 0.0° C. or lower; the crosslinkable functional group is at least one selected from the group consisting of a hydroxyl group, an epoxy group, and a carboxy group; The aliphatic or alicyclic polyisocyanate is a polyisocyanate derived from at least one diisocyanate (b1) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a bifunctional polyol (b2) having a number average molecular weight of 1500 or more, and a trifunctional or higher polyol (b3) having a number average molecular weight of 500 or more. The adhesive resin composition for a surface protective film. ( 2 The content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.01 mass% or more and 25 mass% or less with respect to the total mass of the crosslinkable functional group-containing polymer (A), 1 ) The adhesive resin composition for surface protective films according to claim 1 . ( 3 The weight average molecular weight of the crosslinkable functional group-containing polymer (A) is 2.0×10 5More than 2.5 x 10 6 (1) Or (2) 2. The adhesive resin composition for surface protective films according to claim 1 . ( 4 (1) to (c) are a ratio (NCO / OH) of the molar amount of the isocyanate groups of the diisocyanate (b1) to the total molar amount of the hydroxyl groups of the polyol (b2) and the polyol (b3), of 3 or more and 30 or less. 3 ) The adhesive resin composition for surface protective films according to any one of the preceding claims. ( 5 a mass ratio (b3) / (b2) of the polyol (b3) to the polyol (b2) is 0.1 / 99.9 or more and 99.9 / 0.1 or less, and Relative to 100 parts by mass of the diisocyanate (b1), The content of the polyol (b2) is 0.1 parts by mass or more and 250 parts by mass or less, The content of the polyol (b3) is 0.1 parts by mass or more and 190 parts by mass or less, ( 4 ) an adhesive resin composition for surface protective films. ( 6 The polyol (b2) and the polyol (b3) are one or more polyols selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols, 4 ) or ( 5 ) The adhesive resin composition for surface protective films according to claim 1 . ( 7 (1) to (3) are crosslinking agents (B) each having an isocyanate group content of 1% by mass or more and 10% by mass or less. 6 ) The adhesive resin composition for surface protective films according to any one of the preceding claims. ( 8 (1) to (5) above, the crosslinking agent component (B) is applied onto a glass surface, and after storage for 168 hours in an environment of 23° C. and 65% humidity, a cured film having a thickness of 50 μm is formed, and the Konig hardness in an environment of 23° C. is 60 or less. 7 ) The adhesive resin composition for surface protective films according to any one of the preceding claims. ( 9) a plastic film; An adhesive layer is provided on one or both sides of the plastic film, The adhesive layer is 8 2. A surface protective film comprising a cured product of the pressure-sensitive adhesive resin composition for surface protective films according to claim 1. ( 10 The thickness of the adhesive layer is 1 μm or more and 1000 μm or less. 9 ) A surface protection film as described above. ( 11 The adhesive resin composition for surface protection film is applied onto a 38 μm-thick polyethylene terephthalate film that has been subjected to a release treatment, dried at 135° C. for 3 minutes to cure, and then stored in a 23° C., 50% RH environment for 7 days. The adhesive layer obtained by peeling the release-treated polyethylene terephthalate film from the surface protection film having an adhesive layer with a thickness of 20 μm is then stored in a 23° C., 50% RH environment for 7 days, and then wrapped in a mesh sheet, immersed in ethyl acetate at 23° C. for 1 week, removed, and dried at 120° C. for 2 hours. The gel fraction calculated by the above is 90% by mass or more and 100% by mass or less. ( 9 ) or ( 10 ) A surface protection film as described above. ( 12 The adhesive resin composition for surface protection films was applied onto a 38 μm-thick polyethylene terephthalate film that had been subjected to a release treatment, dried at 135° C. for 3 minutes to cure, and then stored in a 23° C., 50% RH environment for 7 days. The adhesive layer was then laminated to a thickness of 200 μm by peeling off the release-treated polyethylene terephthalate film from the surface protection film having an adhesive layer with a thickness of 20 μm. The adhesive layer was then cut to a width of 10 mm and a length of 40 mm. The laminated adhesive layer was set in a tensile tester with a chuck distance of 10 mm, and a Young's modulus in a tensile test performed at a speed of 300 mm / min in a 23° C. environment was 0.01 N / mm 2 More than 0.22N / mm 2 The following is true: 9 )~( 11 ) A surface protective film according to any one of the preceding claims. (13 The adhesive resin composition for surface protection films is applied onto a polyethylene terephthalate film having a thickness of 25 μm, dried at 135° C. for 3 minutes to be cured, and then stored in an environment of 23° C. and 50% RH for 7 days. The resulting surface protection film having an adhesive layer having a thickness of 20 μm, a width of 25 mm, and a length of 100 mm is then attached to a glass substrate, and pressed once back and forth with a 2 kg roller. After curing at 23° C. for 30 minutes, the 180-degree peel adhesive strength measured at 23° C. and a speed of 300 mm / min is 0.02 N / 25 mm or more and 2.50 N / 25 mm or less. ( 9 )~( 12 ) A surface protective film according to any one of the preceding claims. Effect of the Invention
[0008] According to the adhesive resin composition for surface protection films of the above aspect, it is possible to provide an adhesive resin composition for surface protection films that has good attachment and peelability when used as a surface protection film, and has improved contamination caused by the adhesive during peeling. The surface protection film of the above aspect has an adhesive layer formed by curing the adhesive resin composition for surface protection films, and has good attachment and peelability, and has improved contamination caused by the adhesive during peeling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] In this specification, the term "polyol" refers to a compound having two or more hydroxyl groups (-OH) in one molecule. In addition, in this specification, the term "polyisocyanate" refers to a reaction product in which a plurality of monomer compounds each having two or more isocyanate groups (-NCO) are bonded together. In this specification, unless otherwise specified, "(meth)acrylic" includes both methacrylic and acrylic, and "(meth)acrylate" includes both methacrylate and acrylate.
[0010] <Adhesive resin composition for surface protective film> The adhesive resin composition for a surface protective film of this embodiment contains a crosslinkable functional group-containing polymer (A) and a crosslinker component (B).
[0011] The glass transition temperature Tg of the crosslinkable functional group-containing polymer (A) is −75.0° C. or more and 0.0° C. or less, preferably −72.0° C. or more and 0.0° C. or less, more preferably −72.0° C. or more and −25.0° C. or less, even more preferably −72.0° C. or more and −50.0° C. or less, and particularly preferably −72.0° C. or more and −55.0° C. or less. When the glass transition temperature Tg of the crosslinkable functional group-containing polymer (A) is within the above range, a surface protection film can be obtained that can be applied without air bubbles, is easy to peel off, and has improved contamination by the adhesive during peeling. The glass transition temperature of the crosslinkable functional group-containing polymer (A) can be, for example, a value measured by evaporating the organic solvent and water in a solution in which the crosslinkable functional group-containing polymer (A) is dissolved or dispersed under reduced pressure, vacuum drying the solution, and measuring the temperature at a heating rate of 5°C / min using a differential scanning calorimeter (DSC) measuring device.
[0012] The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 1,400 or more and 200,000 or less and an average number of isocyanate groups of 2.0 or more and 6.5 or less.
[0013] The content of the crosslinking agent component (B) is 0.01 parts by mass or more and 15.0 parts by mass or less, preferably 0.1 parts by mass or more and 13.0 parts by mass or less, more preferably 0.5 parts by mass or more and 12.0 parts by mass or less, even more preferably 0.6 parts by mass or more and 11.0 parts by mass or less, and particularly preferably 0.8 parts by mass or more and 10.0 parts by mass or less, relative to 100 parts by mass of the crosslinking functional group-containing polymer (A). When the content of the crosslinking agent component (B) is within the above numerical range, the curing property, the attachability, and the peelability when made into a surface protective film tend to be excellent, and the staining property tends to be further improved. The content of the crosslinking agent component (B) can be calculated, for example, from the blending amount of the crosslinking agent component (B) used when producing the adhesive resin composition for surface protective film.
[0014] The adhesive resin composition for a surface protective film of this embodiment has the above-mentioned configuration, and thus a surface protective film can be obtained that has good application and peelability and is improved in terms of contamination caused by the adhesive when peeled off.
[0015] <Crosslinkable Functional Group-Containing Polymer (A)> The crosslinkable functional group-containing polymer may be any polymer containing a crosslinkable functional group capable of reacting with the isocyanate group of the polyisocyanate. The crosslinkable functional group is a functional group capable of forming a crosslinked structure with the crosslinking agent component (B), and specifically includes, for example, a hydroxyl group, a thiol group, an amino group, an epoxy group, a carboxyl group, etc., among which, a hydroxyl group, an epoxy group, or a carboxyl group is preferred, and a hydroxyl group is more preferred.
[0016] The crosslinkable functional group-containing polymer is obtained by polymerizing a crosslinkable functional group-containing monomer. The content of the constitutional unit derived from the crosslinkable functional group-containing monomer is preferably 0.01% by mass or more and 25% by mass or less, more preferably 0.1% by mass or more and 20% by mass or less, even more preferably 0.5% by mass or more and 18% by mass or less, and particularly preferably 1.0% by mass or more and 17% by mass or less, based on the total mass of the crosslinkable functional group-containing polymer (A). When the content of the constitutional unit derived from the crosslinkable functional group-containing monomer is within the above numerical range, a surface protection film having good adhesion and peelability and improved contamination by the adhesive during peeling can be obtained. The content of the constitutional unit derived from the crosslinkable functional group-containing monomer can be calculated, for example, from the blending amount of the crosslinkable functional group-containing monomer used in the production of the crosslinkable functional group-containing polymer.
[0017] The crosslinkable functional group-containing polymer (A) is preferably an acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer with a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less, and having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less, or a urethane polymer (A2) having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less.
[0018] The crosslinkable functional group-containing polymer (A) is more preferably an acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less, and having a glass transition temperature Tg of -75.0°C or more and 0.0°C or less.
[0019] [Acrylic polymer (A1)] The acrylic polymer (A1) contains at least one polymerizable (meth)acrylic monomer unit having a crosslinkable functional group as a crosslinkable functional group-containing monomer unit. The crosslinkable functional group preferably contains a hydroxyl group, a carboxyl group, or an epoxy group, and more preferably contains a hydroxyl group.
[0020] The acrylic polymer (A1) may contain a single crosslinkable functional group, or may contain two or more different types of crosslinkable functional groups in combination. That is, the acrylic polymer may be obtained by polymerizing a single polymerizable (meth)acrylic monomer having a crosslinkable functional group, or may be obtained by copolymerizing two or more polymerizable (meth)acrylic monomers having different types of crosslinkable functional groups.
[0021] The acrylic polymer (A1) preferably contains at least one (meth)acrylic acid ester monomer unit having an ester group terminal with 1 to 18 carbon atoms, in addition to the polymerizable (meth)acrylic monomer unit having a crosslinkable functional group. That is, the acrylic polymer (A1) may be obtained by copolymerizing one or more polymerizable (meth)acrylic monomers having a crosslinkable functional group and one or more (meth)acrylic acid ester monomers having an ester group terminal carbon number of 1 to 18. The (meth)acrylic acid ester monomer may or may not have a crosslinkable functional group, but it is preferable that it does not have one.
[0022] The number of carbon atoms at the terminal ester group of the (meth)acrylic acid ester monomer is preferably 1 or more and 18 or less.
[0023] Examples of the polymerizable (meth)acrylic monomer having a crosslinkable functional group include the following (i) to (v). These may be used alone or in combination of two or more. (i) Acrylic esters having a hydroxyl group, such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, 6-hydroxyhexyl acrylate, and 8-hydroxyoctyl acrylate. (ii) Methacrylates having a hydroxyl group, such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, 6-hydroxyhexyl methacrylate, and 8-hydroxyoctyl methacrylate. (iii) (meth)acrylic acid esters having a polyvalent hydroxy group, such as acrylic acid monoester or methacrylic acid monoester of glycerin, and acrylic acid monoester or methacrylic acid monoester of trimethylolpropane. (iv) Unsaturated carboxylic acids such as acrylic acid and methacrylic acid. (v) (meth)acrylic acid esters having an epoxy group, such as glycidyl methacrylate.
[0024] Examples of the (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, Examples of (meth)acrylic acid esters include nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (lauryl (meth)acrylate), tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, benzyl (meth)acrylate, and cyclohexyl (meth)acrylate. These may be used alone or in combination of two or more.
[0025] The acrylic polymer (A1) may further contain, in addition to the polymerizable (meth)acrylic monomer unit having a crosslinkable functional group, other monomer units other than the above-mentioned (meth)acrylic acid ester monomers. That is, the acrylic polymer (A1) is obtained by polymerizing a polymerizable (meth)acrylic monomer having one or more crosslinkable functional groups, or by copolymerizing a polymerizable (meth)acrylic monomer having one or more crosslinkable functional groups with one or more other monomers. The other monomers may or may not have a crosslinkable functional group, but preferably do not have a crosslinkable functional group.
[0026] Examples of the other monomers include the following (i) to (ii). These may be used alone or in combination of two or more. (i) Unsaturated amides such as (meth)acrylamide, N-methylol acrylamide, diacetone acrylamide, and dimethylaminopropyl acrylamide. (ii) Styrene, vinyl toluene, vinyl acetate, (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, dimethylaminoethyl (meth)acrylate, and diethylaminoethyl (meth)acrylate.
[0027] Furthermore, as other monomers copolymerizable with the polymerizable (meth)acrylic monomer having a crosslinkable functional group, polymerizable ultraviolet-stable monomers disclosed in JP-A-1-261409 (Reference 1) and JP-A-3-006273 (Reference 2) may be used.
[0028] Specific examples of the polymerizable ultraviolet-stable monomer include 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-crotonoyl-4-crotonoyloxy-2,2,6,6-tetramethylpiperidine, and 2-hydroxy-4-(3-methacryloxy-2-hydroxypropoxy)benzophenone.
[0029] For example, the above-mentioned monomer components are solution-polymerized in the presence of a known radical polymerization initiator such as a peroxide or an azo compound, and the solution is diluted with an organic solvent, etc., as necessary, to obtain an acrylic polymer.
[0030] When obtaining a water-based acrylic polymer, it can be produced by a known method such as a method of solution polymerization of an olefinically unsaturated compound and converting it into an aqueous phase, emulsion polymerization, etc. In this case, water solubility or water dispersibility can be imparted by neutralizing the acidic moiety of a carboxylic acid-containing monomer such as acrylic acid or methacrylic acid, or a sulfonic acid-containing monomer, etc., with an amine or ammonia.
[0031] The weight average molecular weight Mw(A) of the crosslinkable functional group-containing polymer (A) is 2.0×10 5 More than 2.5 x 10 6 It is preferable that the value is less than 3.0×10 5 Above 2.0×10 6 More preferably, it is 3.5×10 or less. 5 More than 1.8 x 10 6 More preferably, it is 4.0×10 5 More than 1.5 x 10 6 It is particularly preferable that the weight average molecular weight of the crosslinkable functional group-containing polymer (A) is within the above range, so that a surface protection film that is easy to peel off and has improved contamination caused by the adhesive during peeling can be obtained. The weight average molecular weight Mw of the crosslinkable functional group-containing polymer (A) can be measured, for example, by the method described in the examples described later.
[0032] <Crosslinking agent component (B)> The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate (b) having a weight average molecular weight of 1,400 or more and 200,000 or less and an average number of isocyanate groups of 2.0 or more and 6.5 or less.
[0033] The weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is from 1400 to 200000, preferably from 1500 to 100000, more preferably from 2000 to 90000, even more preferably from 3000 to 80000, and particularly preferably from 3200 to 70000. When the weight average molecular weight Mw(b) of the aliphatic or alicyclic polyisocyanate is within the above numerical range, a surface protection film having an adhesive layer with excellent adhesion, easier peeling, and improved contamination resistance can be obtained. The Mw(b) of an aliphatic or alicyclic polyisocyanate is the weight average molecular weight based on polystyrene as determined by GPC measurement.
[0034] The average number of isocyanate groups of the aliphatic or alicyclic polyisocyanate is from 2.0 to 6.5, more preferably from 2.2 to 6.3, even more preferably from 2.4 to 6.0, and particularly preferably from 2.5 to 5.9. When the average number of isocyanate groups of the aliphatic or alicyclic polyisocyanate is within the above numerical range, a surface protection film having an adhesive layer with excellent adhesion, easier peeling, and improved contamination resistance can be obtained.
[0035] The average number (fn) of isocyanate groups of an aliphatic or alicyclic polyisocyanate can be calculated using the following formula. In the formula, "Mn" indicates the number average molecular weight of the aliphatic or alicyclic polyisocyanate, and "NCO%" indicates the isocyanate group content of the aliphatic or alicyclic polyisocyanate. The number average molecular weight Mn of the aliphatic or alicyclic polyisocyanate is the weight average molecular weight based on polystyrene measured by GPC. The method for measuring NCO% will be described later.
[0036] [fn] = [Mn] × [NCO%] / 4200
[0037] The aliphatic or alicyclic polyisocyanate (b) is preferably a polyisocyanate derived from at least one diisocyanate (b1) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a bifunctional polyol (b2) having a number average molecular weight of 1,500 or more, and a tri- or higher functional polyol (b3) having a number average molecular weight of 500 or more.
[0038] The ratio NCO / OH of the molar amount of isocyanate groups in the diisocyanate (b1) to the total molar amount of hydroxyl groups in the polyol (b2) and the polyol (b3) is preferably from 3 to 30, more preferably from 4 to 28, even more preferably from 5 to 27, and particularly preferably from 6 to 25. When the NCO / OH is within the above numerical range, a surface protective film having an adhesive layer with excellent adhesion, easier peeling, and improved contamination resistance can be obtained.
[0039] The aliphatic or alicyclic polyisocyanate (b) may be a polyisocyanate having, in one molecule, all of the constituent units derived from a diisocyanate, a polyol (b2), and a polyol (b3), or may be a mixture of polyisocyanates having, in one molecule, a constituent unit derived from at least one selected from the group consisting of a diisocyanate, a polyol (b2), and a polyol (b3).
[0040] The aliphatic or alicyclic polyisocyanate (b) may have at least one structure selected from the group consisting of an allophanate structure, a uretdione structure, an iminooxadiazinedione structure, an isocyanurate structure, a urea structure, a urethane structure, and a biuret structure. Among these, it is preferable that the polyisocyanate has at least one structure selected from the group consisting of a urethane structure, an allophanate structure, a biuret structure, a urea structure, and an isocyanurate group, and more preferably contains a urethane structure.
[0041] [Diisocyanate (b1)] The diisocyanate (b1) is at least one selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates.
[0042] Examples of the aliphatic diisocyanate include, but are not limited to, 1,4-diisocyanatobutane, 1,5-diisocyanatopentane, ethyl (2,6-diisocyanato)hexanoate, 1,6-diisocyanatohexane (hereinafter sometimes abbreviated as "HDI"), 1,9-diisocyanatononane, 1,12-diisocyanatododecane, 2,2,4- or 2,4,4-trimethyl-1,6-diisocyanatohexane, etc. These aliphatic diisocyanates may be used alone or in combination of two or more.
[0043] Examples of alicyclic diisocyanates include, but are not limited to, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane (hereinafter sometimes abbreviated as "hydrogenated XDI"), 1,3- or 1,4-diisocyanatocyclohexane, 3,5,5-trimethyl-1-isocyanato-3-(isocyanatomethyl)cyclohexane (hereinafter sometimes abbreviated as "IPDI"), 4-4'-diisocyanato-dicyclohexylmethane (hereinafter sometimes abbreviated as "hydrogenated MDI"), 2,5- or 2,6-diisocyanatomethylnorbornane, etc. These alicyclic diisocyanates may be used alone or in combination of two or more.
[0044] These aliphatic diisocyanates and alicyclic diisocyanates may be used alone, or two or more of them may be used in combination. From the viewpoint of flexibility, the mass ratio of the alicyclic polyisocyanate to the aliphatic diisocyanate is preferably 0 / 100 or more and 30 / 70 or less.
[0045] Among these, the diisocyanate is preferably HDI, IPDI, hydrogenated XDI, or hydrogenated MDI, more preferably HDI or IPDI, and even more preferably HDI.
[0046] In the production of polyisocyanates, in addition to the diisocyanates described above, isocyanate monomers such as those shown below may be further used. (1) Aromatic diisocyanates such as diphenylmethane-4,4'-diisocyanate (MDI), 1,5-naphthalene diisocyanate, tolylene diisocyanate (TDI), xylylene diisocyanate, and m-tetramethylxylylene diisocyanate (TMXDI). (2) Triisocyanates such as 4-isocyanatomethyl-1,8-octamethylene diisocyanate (hereinafter sometimes referred to as "NTI"), 1,3,6-hexamethylene triisocyanate (hereinafter sometimes referred to as "HTI"), bis(2-isocyanatoethyl) 2-isocyanatoglutarate (hereinafter sometimes referred to as "GTI"), and lysine triisocyanate (hereinafter sometimes referred to as "LTI").
[0047] [Polyol (b2) and polyol (b3)] The polyol (b2) has a number average molecular weight of 1500 or more and is a difunctional polyol (diol). The polyol (b3) has a number average molecular weight of 500 or more and is a polyol having three or more functional groups.
[0048] The number average molecular weight of the polyol (b2) is at least 1500, and preferably at least 1700. When the number average molecular weight of the polyol (b2) is at least the above lower limit, the hardness of the cured film obtained by curing the polyisocyanate alone is low and the flexibility is good. On the other hand, the upper limit of the number average molecular weight of the polyol (b2) is not particularly limited, but may be, for example, 7,000, and 6,500 is more preferable. The number average molecular weight Mn of the polyol (b2) is, for example, a number average molecular weight based on polystyrene standards as measured by GPC. When two or more kinds of polyols (b2) are used in combination, the number average molecular weight of the mixture is calculated.
[0049] The number average molecular weight of the polyol (b3) is not less than 500, and preferably not less than 800. When the number average molecular weight of the polyol (b3) is not less than the above lower limit, the hardness of the cured film obtained by curing the polyisocyanate alone is low and the flexibility is good. On the other hand, the upper limit of the number average molecular weight of the polyol (b3) is not particularly limited, but can be, for example, 4,000, preferably 3,000, and more preferably 2,500. The number average molecular weight Mn of the polyol (b3) is, for example, a number average molecular weight based on polystyrene standards as measured by GPC. When two or more kinds of polyols (b3) are used in combination, the number average molecular weight of the mixture is calculated.
[0050] The polyol (b2) is preferably at least one bifunctional polyol (diol) selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols, and is more preferably a bifunctional polyester polyol.
[0051] Examples of bifunctional polyester polyols include the following polyester polyols (1) and (2). (1) Polyester polyols obtained by the condensation reaction of a dibasic acid, or a mixture of two or more kinds, with a dihydric alcohol, or a mixture of two or more kinds. (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone with a dihydric alcohol. Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, trimethylpentanediol, and cyclohexanediol.
[0052] Among these, as the difunctional polyester polyol, a difunctional polycaprolactone polyol is preferable.
[0053] Commercially available bifunctional polycaprolactone polyols include, for example, trade names "PLACCEL 210" (number average molecular weight 1000), "PLACCEL 220" (number average molecular weight 2000), "PLACCEL 230" (number average molecular weight 3000), and "PLACCEL 240" (number average molecular weight 4000), manufactured by Daicel Corporation.
[0054] The polyol (b3) may be a polyol having three or more functionalities, preferably a polyol having three or more and ten or less functionalities, more preferably a polyol having three or more and seven or less functionalities, even more preferably a polyol having three or more and five or less functionalities, particularly preferably a polyol having three or more and four or less functionalities, and most preferably a trifunctional polyol (triol). The trifunctional polyol (triol) is preferably at least one trifunctional polyol (triol) selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols, more preferably a trifunctional polyether polyol or polyester polyol, and even more preferably a trifunctional polyester polyol.
[0055] Examples of trifunctional polyester polyols include the following polyester polyols (1) and (2). (1) Polyester polyols obtained by the condensation reaction of a dibasic acid, either alone or in a mixture of two or more kinds, with a trihydric alcohol, either alone or in a mixture of two or more kinds. (2) Polycaprolactone polyol obtained by ring-opening polymerization of ε-caprolactone with a trihydric alcohol. Examples of the dibasic acid include carboxylic acids such as succinic acid, adipic acid, dimer acid, maleic anhydride, phthalic anhydride, isophthalic acid, terephthalic acid, and 1,4-cyclohexanedicarboxylic acid. Examples of the trihydric alcohol include trimethylolpropane, glycerin, pentaerythritol, 2-methylolpropanediol, and ethoxylated trimethylolpropane.
[0056] Among them, as the trifunctional polyester polyol, a trifunctional polycaprolactone polyol is preferable.
[0057] Commercially available trifunctional polycaprolactone polyols include, for example, trade names "PLACCEL 305" (number average molecular weight 550), "PLACCEL 308" (number average molecular weight 850), "PLACCEL 309" (number average molecular weight 900), "PLACCEL 312" (number average molecular weight 1250), and "PLACCEL 320" (number average molecular weight 2000), manufactured by Daicel Corporation.
[0058] In the aliphatic or alicyclic polyisocyanate (b), the mass ratio of the polyol (b2) to the polyol (b3) (the mass ratio of (b2) / (b3)) is preferably from 0.1 / 99.9 to 99.9 / 0.1, more preferably from 1 / 99 to 99 / 1, even more preferably from 3 / 97 to 90 / 10, particularly preferably from 5 / 95 to 85 / 15, and most preferably from 7 / 93 to 80 / 20. When the mass ratio of (b2) / (b3) is equal to or greater than the lower limit, the hardness of the cured film obtained by curing the polyisocyanate alone is low and the flexibility is better. In addition, a surface protection film having better adhesion and flexibility is obtained. On the other hand, when the mass ratio of (b2) / (b3) is equal to or less than the upper limit, the surface protection film having better adhesion, flexibility and cohesion is obtained. The mass ratio of (b2) / (b3) can be calculated, for example, from the blending amounts of each polyol during the production of the polyisocyanate.
[0059] In the aliphatic or alicyclic polyisocyanate (b), the content (charged amount) of the polyol (b2) relative to 100 parts by mass of the diisocyanate is preferably 0.1 parts by mass or more and 250 parts by mass or less, more preferably 0.5 parts by mass or more and 240 parts by mass or less, even more preferably 1.0 parts by mass or more and 230 parts by mass or less, and particularly preferably 3.0 parts by mass or more and 220 parts by mass or less. When the content of polyol (b2) is equal to or more than the lower limit, the hardness of the cured film obtained by curing the polyisocyanate alone is low and the flexibility is better. Also, a surface protection film having better adhesion and curability can be obtained. On the other hand, when the content of polyol (b2) is equal to or less than the upper limit, the polyisocyanate can be maintained in a liquid state without gelling during production, and the flexibility of the surface protection film when made into the polyisocyanate is better. The content of polyol (b2) can be calculated, for example, from the amounts of diisocyanate and polyol (b2) blended during the production of the polyisocyanate.
[0060] In the aliphatic or alicyclic polyisocyanate (b), the content (charged amount) of the polyol (b3) relative to 100 parts by mass of the diisocyanate is preferably 0.1 parts by mass or more and 190 parts by mass or less, more preferably 10 parts by mass or more and 180 parts by mass or less, even more preferably 20 parts by mass or more and 190 parts by mass or less, and particularly preferably 25 parts by mass or more and 180 parts by mass or less. When the content of polyol (b3) is equal to or less than the upper limit, the polyisocyanate can be maintained in a liquid state without gelation during production, and the curability and flexibility of the surface protection film when made into the film are better. On the other hand, when the content of polyol (b3) is equal to or more than the lower limit, the hardness of the cured film obtained by curing the polyisocyanate alone is low and the flexibility is better. In addition, a surface protection film having excellent adhesion and curability can be obtained. The content of polyol (b3) can be calculated, for example, from the amounts of diisocyanate and polyol (b3) blended during the production of the polyisocyanate.
[0061] [Production method of crosslinking agent component (B)] When the crosslinking agent component (B) is an aliphatic or alicyclic polyisocyanate (b), it is obtained by reacting the above diisocyanate (b1), polyol (b2), and polyol (b3). Hereinafter, polyol (b2) and polyol (b3) may be collectively referred to simply as polyol.
[0062] The polyol (b2) and the polyol (b3) can be used alone or as a mixture. When used as a mixture, they may be mixed before reacting with the diisocyanate, or each polyol may be reacted with the diisocyanate alone to form a polyisocyanate and then mixed. That is, examples of methods for producing polyisocyanates include a method of simultaneously reacting a diisocyanate with a polyol (b2) and a polyol (b3) to obtain a polyisocyanate; a method of mixing a reaction product of a diisocyanate with a polyol (b2) and a reaction product of a diisocyanate with a polyol (b3) to obtain a polyisocyanate; and a method of reacting a diisocyanate with a polyol (b2) or a polyol (b3) and then further reacting the remaining polyol to obtain a polyisocyanate.
[0063] The amounts of polyol (b2) and polyol (b3) are preferably such that the mass ratio of polyol (b2) to polyol (b3) falls within the above range.
[0064] In the reaction, the molar ratio of isocyanate groups of the diisocyanate to hydroxyl groups of the polyol (b2) and polyol (b3) (molar ratio of isocyanate groups / hydroxyl groups) is preferably from 3 to 30, more preferably from 4 to 25, even more preferably from 5 to 23, and particularly preferably from 6 to 22. When the NCO / OH is within the above numerical range, a surface protective film having an adhesive layer with excellent adhesion, easier peeling, and improved contamination resistance can be obtained.
[0065] The reaction between polyol and diisocyanate is carried out as follows. The reaction temperature is usually from room temperature (about 23° C.) to 200° C., and preferably from 60° C. to 130° C. If the reaction temperature is equal to or higher than the lower limit, the reaction time is shorter, while if the reaction temperature is equal to or lower than the upper limit, an increase in the viscosity of the polyisocyanate due to undesirable side reactions can be more effectively prevented, and coloration of the polyisocyanate produced can also be more effectively prevented.
[0066] The reaction may be carried out without a solvent or in any solvent inert to the isocyanate group, and if necessary, a known catalyst may be used to promote the reaction between the isocyanate group and the hydroxyl group.
[0067] [Physical properties of crosslinking agent component (B)] The isocyanate group content (NCO group content) of the crosslinking agent component (B), in a state substantially free of solvent or diisocyanate, is preferably from 1 mass % to 10 mass % based on the total mass of the crosslinking agent component (B), more preferably from 2 mass % to 9.5 mass %, even more preferably from 2.2 mass % to 9.0 mass %, and particularly preferably from 2.5 mass % to 8.5 mass %. The NCO group content can be determined, for example, by reacting the isocyanate groups in the crosslinking agent component (B) with an excess of an amine (such as dibutylamine) and back-titrating the remaining amine with an acid such as hydrochloric acid.
[0068] Only the above-mentioned crosslinking agent component (B) is applied onto glass, and after storage for 168 hours in an environment of 23°C and 65% humidity, the Konig hardness of the cured film having a thickness of 50 μm formed by the reaction between moisture in the air and the polyisocyanate composition in an environment of 23°C is 60 or less, preferably 57 or less, more preferably 55 or less, and even more preferably 54 or less. When the Konig hardness is equal to or less than the upper limit, the hardness is low and the flexibility is excellent.
[0069] [Isocyanate group / Crosslinkable functional group] The molar ratio of the isocyanate group of the crosslinking agent component (B) to the crosslinkable functional group (particularly, hydroxyl group) of the crosslinkable functional group-containing polymer (A) contained in the adhesive resin composition for surface protection film of this embodiment (the molar ratio of isocyanate group / crosslinkable functional group) is determined based on the physical properties of the required surface protection film, but is usually 0.005 or more and 50 or less.
[0070] <Other ingredients> The adhesive resin composition for a surface protective film of this embodiment may further contain other additives. Examples of other additives include curing agents other than the crosslinking agent component (B) capable of reacting with the crosslinkable functional group-containing polymer (A), curing catalysts, solvents, pigments (extender pigments, coloring pigments, metallic pigments, etc.), tackifying resins, photopolymerization initiators, ultraviolet absorbers, light stabilizers, radical stabilizers, yellowing inhibitors that suppress coloring during the baking process, coating surface adjusters, flow adjusters, pigment dispersants, defoamers, thickeners, film-forming assistants, and the like.
[0071] Examples of the curing agent include melamine resins, urea resins, epoxy group-containing compounds or resins, carboxy group-containing compounds or resins, acid anhydrides, alkoxysilane group-containing compounds or resins, and hydrazide compounds.
[0072] The curing catalyst may be a basic compound or a Lewis acid compound. Examples of the basic compound include metal hydroxides, metal alkoxides, metal carboxylates, metal acetylacetinates, hydroxides of onium salts, onium carboxylates, halides of onium salts, metal salts of active methylene compounds, onium salts of active methylene compounds, aminosilanes, amines, phosphines, etc. As the onium salts, ammonium salts, phosphonium salts, or sulfonium salts are preferable. Examples of the Lewis acid compound include an organotin compound, an organozinc compound, an organotitanium compound, and an organozirconium compound.
[0073] Examples of the solvent include 1-methylpyrrolidone, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monomethyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol diethyl ether, diethylene glycol diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether (DPDM), propylene glycol dimethyl ether, methyl ethyl ketone, acetone, and the like. Examples of the solvent include methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethanol, methanol, iso-propanol, 1-propanol, iso-butanol, 1-butanol, tert-butanol, 2-ethylhexanol, cyclohexanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, ethyl acetate, isopropyl acetate, butyl acetate, toluene, xylene, pentane, iso-pentane, hexane, iso-hexane, cyclohexane, solvent naphtha, mineral spirits, etc. These solvents may be used alone or in combination of two or more.
[0074] In addition, known pigments (extender pigments, colored pigments, metallic pigments, etc.), ultraviolet absorbers, light stabilizers, radical stabilizers, yellowing inhibitors that suppress coloring during the baking process, coating surface conditioners, flow conditioners, pigment dispersants, defoamers, thickeners, and film-forming aids can be appropriately selected and used.
[0075] <Method for producing adhesive resin composition for surface protective film> The adhesive resin composition for surface protection films can be produced by a conventional method, for example, a melt-kneading method using a general mixer such as a Banbury mixer, a single screw extruder, a twin screw extruder, a co-kneader, or a multi-screw extruder, or a method in which each component is dissolved or dispersed and mixed, then coated on a substrate film with a coater or the like, and the solvent is then removed by heating.
[0076] The adhesive resin composition for surface protection film of the present embodiment may be foamed in order to achieve the effects of weight reduction, flexibility, and improved adhesion. Foaming methods include chemical methods, physical methods, and the use of thermally expandable microballoons. In each case, air bubbles can be distributed inside the material by adding a chemical foaming agent such as an inorganic foaming agent or an organic foaming agent, or a physical foaming agent, or by adding a thermally expandable microballoon.
[0077] In addition, hollow fillers (pre-expanded balloons) may be added to make the material lighter, more flexible, and more adhesive.
[0078] The adhesive resin composition for surface protective film of this embodiment may contain a tackifier resin to adjust adhesive strength and cohesive strength. Examples of the tackifier resin include rosin-based tackifier resins, terpene-based tackifier resins, petroleum-based tackifier resins, and styrene-based tackifier resins. These tackifier resins may be used alone or in combination of two or more. The softening point of the tackifier resin is preferably 90°C or higher and 160°C or lower.
[0079] <Surface protection film> The surface protection film of this embodiment includes a plastic film and an adhesive layer on one or both sides of the plastic film. The adhesive layer is made of a cured product of the adhesive resin composition for surface protection films described above.
[0080] In the surface protection film of this embodiment, the adhesive layer is easy to peel off, and contamination caused by the adhesive during peeling is improved.
[0081] In the surface protection film of this embodiment, the thickness of the adhesive layer can be appropriately determined depending on the application, but is preferably 1 μm or more and 1000 μm or less, more preferably 2 μm or more and 900 μm or less, even more preferably 3 μm or more and 800 μm or less, and particularly preferably 4 μm or more and 700 μm or less.
[0082] The surface protective film of this embodiment can be produced, for example, by applying the adhesive resin composition for surface protective films onto a substrate, drying it as necessary, and then curing it. Examples of the method for applying the adhesive resin composition for surface protective films to a substrate include a method of applying the composition using an applicator, a roll coater, a knife coater, a gravure coater, etc. When drying is performed after the application, examples of the method include a heat drying method in which the obtained laminate is placed in a dryer or the like and dried for 1 minute to 30 minutes at a temperature of 50° C. to 150° C. Other drying methods include, for example, natural drying, hot air drying, infrared drying, etc.
[0083] The heating temperature during curing may be 70°C or higher and 160°C or lower, 75°C or higher and 155°C or lower, or 80°C or higher and 150°C or lower.
[0084] In the surface protection film of this embodiment, the adhesive resin composition for surface protection film is applied onto a 38 μm-thick polyethylene terephthalate film that has been subjected to a release treatment, dried at 135 ° C for 3 minutes to cure, and then stored for 7 days under a 23 ° C, 50% RH environment. The adhesive layer obtained by peeling off the release-treated polyethylene terephthalate film from the surface protection film having an adhesive layer with a thickness of 20 μm is then stored for 7 days under a 23 ° C, 50% RH environment, and then wrapped in a mesh sheet, immersed in ethyl acetate at 23 ° C for 1 week, removed, and dried at 120 ° C for 2 hours. The gel fraction calculated by the above method is preferably 90.0 mass % or more and 100.0 mass % or less. When the gel fraction is equal to or more than the above lower limit, the curability is superior. The gel fraction referred to here is the percentage of the mass of the adhesive layer after immersion in ethyl acetate and drying relative to the mass of the adhesive layer before immersion in ethyl acetate.
[0085] In the surface protection film of the present embodiment, the adhesive resin composition for surface protection film is applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 135° C. for 3 minutes to harden, and then stored in a 23° C., 50% RH environment for 7 days. The release-treated polyethylene terephthalate film is peeled off from the surface protection film having an adhesive layer of 20 μm, and the adhesive layer is laminated to a thickness of 200 μm. The adhesive layer is then cut to a width of 10 mm and a length of 40 mm. The laminated adhesive layer is set in a tensile tester with a chuck distance of 10 mm, and a Young's modulus in a tensile test performed at a speed of 300 mm / min in a 23° C. environment is 0.22 N / mm 2 It is preferable that the resistance is less than 0.20 N / mm 2 More preferably, it is 0.15 N / mm 2 When the Young's modulus is equal to or less than the above upper limit, the elastic modulus is lower, and the adhesiveness and conformability to the adherend are more excellent. The lower limit of the Young's modulus is preferably as small as possible. For example, the lower limit is 0.01 N / mm 2 It can be said that:
[0086] The surface protection film of this embodiment is prepared by applying the adhesive resin composition for surface protection film to a polyethylene terephthalate film having a thickness of 25 μm, drying and curing the composition at 135° C. for 3 minutes, and then storing the adhesive layer having a thickness of 20 μm, a width of 25 mm, and a length of 100 mm for 7 days under an environment of 23° C. and 50% RH. The adhesive layer is then laminated to glass as an adherend, pressed once back and forth with a 2 kg roller, and aged at 23° C. for 30 minutes. The 180° peel adhesive strength measured at 23° C. and a speed of 300 mm / min is preferably 0.02 N / 25 mm or more and 2.50 N / 25 mm or less, more preferably 0.03 N / 25 mm or more and 2.40 N / 25 mm or less, and even more preferably 0.04 N / 25 mm or more and 2.30 N / 25 mm or less. By having the 180° peel adhesive strength within the above numerical range, the peelability can be improved.
[0087] As described above, the surface protection film of this embodiment is easy to peel off and has improved resistance to contamination by the adhesive during peeling, and is therefore suitably used, for example, as a surface protection film for optical members. EXAMPLES
[0088] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples.
[0089] [Physical Properties 1] (glass transition temperature Tg) The glass transition temperature of the acrylic polymer (A) was determined by evaporating the organic solvent and water in a solution of the acrylic polymer (A) under reduced pressure, vacuum drying the resulting solution, and measuring the temperature at a heating rate of 5°C / min using a differential scanning calorimeter (DSC) measurement device.
[0090] [Physical Properties 2] (Number average molecular weight and weight average molecular weight) The number average molecular weight and weight average molecular weight are those measured by gel permeation chromatography (GPC) using the following apparatus, using polystyrene as a standard.
[0091] (Measurement conditions) Equipment: Tosoh Corporation, HLC-802A Column: Tosoh Corporation, G1000HXL x 1 G2000HXL x 1 G3000HXL x 1 Carrier: Tetrahydrofuran Detection method: Differential refractometer
[0092] [Physical Properties 3] (Isocyanate group content) First, 2 g to 3 g of the measurement sample was weighed out (Wg) in a flask. Then, 20 mL of toluene was added to dissolve the measurement sample. Then, 20 mL of a 2N toluene solution of di-n-butylamine was added, mixed, and left at room temperature for 15 minutes. Then, 70 mL of isopropyl alcohol was added and mixed. Then, this liquid was titrated with a 1N hydrochloric acid solution (factor F) as an indicator. The titration value obtained was V2 mL. Then, the titration value obtained without the sample was V1 ml. Then, the isocyanate group content (NCO%) (mass%) of the crosslinking agent component (B) was calculated from the following formula.
[0093] "Isocyanate group content (mass%)" = (V1-V2) x F x 42 / (W x 1000) x 100
[0094] [Physical Properties 4] (Average number of isocyanate functional groups) The average number of isocyanate functional groups (average NCO number) of the crosslinking agent component (B) was calculated by the following formula. In the formula, "Mn" means number average molecular weight, and the value measured in the above "Physical Properties 2" was used. "NCO%" was the value calculated in the above "Physical Properties 3".
[0095] "Average number of isocyanate functional groups" = (Mn x NCO% x 0.01) / 42
[0096] [Preparation of cured film of crosslinker component (B)] Each crosslinking agent component (B) was applied onto a glass plate using an applicator, and after storing the mixture in an environment of 23°C and 65% humidity for 168 hours, it was further heated at 50°C for 24 hours to obtain a cured film having a thickness of 50 μm.
[0097] [Physical Properties 5] (Konig hardness) For each cured film, the Konig hardness (times) was measured in an environment of 23° C. using a Konig hardness tester (Pendulum hardness tester manufactured by BYK Gardner).
[0098] <Evaluation method> [Preparation of surface protection film 1] Each adhesive resin composition for surface protection films was applied to a 38 μm-thick release-treated PET film using an applicator so that the thickness after drying would be 20 μm, and then dried for 3 minutes at 135° C. Thereafter, the film was stored for 7 days in an environment of 23° C. and 50% RH to obtain a surface protection film 1 for gel fraction measurement and tensile test. The release-treated PET film was peeled off and subjected to each evaluation.
[0099] [Preparation of surface protection film 2] Each adhesive resin composition for surface protection films was applied onto a 25 μm thick polyethylene terephthalate (PET) film using an applicator so that the thickness after drying would be 20 μm, and then dried for 3 minutes at 135° C. Thereafter, the film was stored in an environment of 23° C. and 50% RH for 7 days to obtain surface protection film 2 for measuring 180° peel adhesive strength.
[0100] [Rating 1] (Gel fraction) About 0.1 g to 0.2 g of the adhesive layer obtained by peeling off the peel-treated PET film from the surface protective film 1 obtained in the above "Preparation of Surface Protective Film 1" was collected, wrapped in a mesh sheet, immersed in ethyl acetate for one week, and then dried for two hours at 120° C. Next, the percentage of the mass of the adhesive layer dried after immersion in ethyl acetate to the mass of the adhesive layer before immersion in ethyl acetate was calculated as the gel fraction (mass%). The curability was evaluated as good when the gel fraction was 90% by mass or more.
[0101] [Rating 2] (Tensile test: Young's modulus) The adhesive layer obtained by peeling off the peel-treated PET film from the surface protection film 1 obtained in the above "Preparation of Surface Protection Film 1" was laminated to a thickness of 200 μm and cut to a width of 10 mm and a length of 40 mm. The laminated adhesive layer was then set in a tensile tester so that the chuck distance was 10 mm, and the Young's modulus was measured at a speed of 300 mm / min using the tensile tester in a 23°C environment. Young's modulus: 0.22N / mm 2 The following were evaluated as having good adhesion and conformability to the adherend.
[0102] [Rating 3] (180 degree peel adhesion and stain resistance) The surface protection film 2 obtained in the above "Preparation of surface protection film 2" was cut to a width of 25 mm and a length of 100 mm to obtain a test piece. The test piece was then attached to a glass substrate, and a 2 kg roller was rolled back and forth once to press the test piece onto the glass. After curing for 30 minutes at 23°C, the 180° peel adhesive strength was measured using a tensile tester at a speed of 300 mm / min. A value of 0.02 N / 25 mm or more and 2.50 N / 25 mm was evaluated as having good peelability.
[0103] Next, the surface of the glass adherend after measuring the 180° peel adhesive strength was visually observed and the stain resistance was evaluated according to the following evaluation criteria.
[0104] (Evaluation Criteria) ○: No contamination (no visible adhesive remains on the glass surface) ×: Contamination occurred (adhesive remains visible on the glass surface)
[0105] <Synthesis of crosslinkable functional group-containing polymer (A)> [Synthesis Example 1-1] (Synthesis of Acrylic Polymer A-1) Into a four-neck flask equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, and a cooling tube, 96 parts by mass of 2-ethylhexyl acrylate (2EHA) and 4 parts by mass of 4-hydroxybutyl acrylate (4HBA) were added, and 240 parts by mass of ethyl acetate was added as a solvent. Next, while stirring under a nitrogen gas atmosphere, 0.15 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the reaction was carried out at 65°C for 8 hours. After the reaction, the mixture was cooled to obtain an acrylic polymer A-1 with a solid content concentration of 30.0% by mass.
[0106] [Synthesis Examples 1-2 to 1-8] (Synthesis of Acrylic Polymers A-1 to A-8) Each acrylic polymer was synthesized in the same manner as in Synthesis Example 1-1, except that the blending ratio of each monomer was as shown in Table 1.
[0107] The compositions and physical properties of the synthesized acrylic polymers are shown in the following Table 1. In Table 1, the abbreviations of the monomers represent the following compounds.
[0108] (Crosslinkable Functional Group-Containing Monomer (a1)) 4HBA: 4-Hydroxybutyl acrylate HEA: Hydroxyethyl acrylate
[0109] ((Meth)acrylic acid ester monomer (a2)) 2EHA: 2-Ethylhexyl acrylate iOA: isooctyl acrylate iNA: Isononyl acrylate MA: Methyl acrylate BA: Butyl acrylate
[0110] [Table 1]
[0111] <Synthesis of crosslinking agent component (B)> [Synthesis Example 2-1] (Synthesis of polyisocyanate component B-1) In a four-neck flask equipped with a thermometer, a stirring blade and a reflux condenser, 100 parts by mass of HDI was charged under a nitrogen gas flow, and 4.7 parts by mass of a bifunctional polycaprolactone polyol (manufactured by Daicel Corporation, trade name "Placcel 220", number average molecular weight 2000) (hereinafter, sometimes referred to as "polyol b2-1" or simply "b2-1") and 33 parts by mass of a trifunctional polycaprolactone polyol (manufactured by Daicel Corporation, trade name "Placcel 308", number average molecular weight 850) (hereinafter, sometimes referred to as "polyol b3-1" or simply "b3-1") (amount such that the molar ratio of the isocyanate group of HDI to the hydroxyl group of polyol b2-1 and polyol b3-1 is 10.0) were stirred while maintaining the temperature in the reactor at 90 ° C. for 110 minutes. The reaction was stopped when the yield reached 40% by mass. The reaction liquid was filtered, and then unreacted HDI was removed using a thin-film distillation apparatus to obtain a polyisocyanate component B-1.
[0112] [Synthesis Examples 2-2 to 2-4, and Synthesis Example 2-8] (Synthesis of polyisocyanate components B-2 to B-4, and B-8) Except for the types and blending ratios of raw materials as shown in Table 2, the same method as in Synthesis Example 2-1 was used to synthesize each polyisocyanate component.
[0113] [Synthesis Example 2-5] (Synthesis of polyisocyanate component B-5) A four-neck flask equipped with a thermometer, a stirring blade, and a reflux condenser was charged with 100 parts by mass of HDI and 8.9 parts by mass of trimethylolpropane (hereinafter sometimes referred to as "polyol b3-3" or simply "b3-3") under a nitrogen stream, and the temperature inside the reactor was maintained at 75°C for 5 hours with stirring to carry out a urethane reaction. The reaction liquid was filtered, and then unreacted HDI was removed using a thin-film evaporator to obtain an isocyanurate-type polyisocyanate (hereinafter sometimes referred to as "polyisocyanate component B-5").
[0114] [Synthesis Example 2-6] (Synthesis of polyisocyanate component B-6) In a four-neck flask equipped with a thermometer, stirring blade, and reflux condenser, 100 parts by mass of HDI was charged under a nitrogen stream, and the temperature inside the reactor was maintained at 62°C while stirring. 0.095 parts by mass of trimethylbenzylammonium hydroxide was added and reacted for 4 hours. After that, when the conversion rate reached 38% by mass, 0.02 parts by mass of phosphoric acid was added to stop the reaction. After filtering the reaction liquid, unreacted HDI was removed using a thin-film evaporator to obtain an isocyanurate-type polyisocyanate (hereinafter, sometimes referred to as "polyisocyanate component B-6").
[0115] [Synthesis Example 2-7] (Synthesis of polyisocyanate component B-7) In a four-neck flask equipped with a thermometer, stirring blade and reflux condenser, 100 parts by mass of HDI was charged under a nitrogen stream, and 30 parts by mass of polyol b3-1 (an amount such that the molar ratio of the isocyanate group of HDI to the hydroxyl group of polyol b3-1 is 11.4) was stirred while maintaining the temperature in the reactor at 95°C for 80 minutes. The reaction was stopped when the yield reached 39% by mass. After filtering the reaction liquid, the unreacted HDI was removed using a thin-film distillation apparatus to obtain polyisocyanate component B-7.
[0116] The composition and physical properties of each synthesized polyisocyanate component are shown in Table 2. In Table 2, the polyols are the following compounds.
[0117] (Polyol (b2)) b2-1: Difunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "Placcel 220", number average molecular weight 2000 b2-2: Polytetramethylene ether glycol, manufactured by Asahi Glass Co., Ltd., product name "Excenol 2020", number average molecular weight 2000
[0118] (Polyol (b3)) b3-1: Trifunctional polycaprolactone polyol, Daicel Corporation, trade name "Placcel 308", number average molecular weight 850 b3-2: Trifunctional polycaprolactone polyol, manufactured by Daicel Corporation, trade name "Placcel 312", number average molecular weight 1250
[0119] (Polyol (b3')) b3'-1: Trimethylolpropane (TMP)
[0120] [Table 2]
[0121] <Production of Adhesive Resin Composition for Surface Protective Film> [Example 1] (Production of adhesive resin composition S-a1 for surface protective film) To 100 parts by mass of acrylic polymer A-1, 3.0 parts by mass of polyisocyanate component B-3, 0.1 parts by mass of dioctyltin dilaurate (DOT, manufactured by Nitto Chemical Industry Co., Ltd., product name "Neostan U-810") as a crosslinking accelerator, and ethyl acetate were added to obtain an adhesive resin composition S-a1 for surface protection films with a solid content of 30% by mass.
[0122] [Examples 2 to 8 and Comparative Examples 1 to 4] (Production of Adhesive Resin Compositions S-a2 to S8 and S-b1 to S-b4 for Surface Protective Films) Each adhesive resin composition for surface protection films was produced using the same method as in Example 1, except that the types and blending ratios of the crosslinkable functional group-containing polymer (A) and the crosslinking agent component (B) were as shown in Tables 3 and 4.
[0123] The compositions and evaluation results of each adhesive resin composition for surface protective films are shown in Tables 3 and 4.
[0124] [Table 3]
[0125] [Table 4]
[0126] As can be seen from Tables 3 and 4, the surface protective films using the adhesive resin compositions S-a1 to S-a8 (Examples 1 to 8) for surface protective films, which contain a crosslinkable functional group-containing polymer (A) having a glass transition temperature Tg of -68.7°C or more and -57.3°C or less, and an aliphatic polyisocyanate having a weight average molecular weight of 4180 or more and 21500 or less and an average number of isocyanate groups of 3.8 or more and 4.6 or less, were excellent in curability, attachment property, peelability, and contamination resistance. In addition, in a comparison of surface protection films using adhesive resin compositions S-a2, S-a5, and S-a6 (Examples 2, 5, and 6) for surface protection films containing different types of crosslinkable functional group-containing polymer (A), the lower the glass transition temperature or the smaller the weight average molecular weight, the smaller the Young's modulus, the lower the elastic modulus, and the better the adhesion and conformability to the substrate.
[0127] On the other hand, the surface protection films using adhesive resin compositions S-b1 and S-b3 (Comparative Examples 1 and 3) for surface protection films containing 3.0 parts by mass each of polyisocyanate components B-5 to B-6 having a weight average molecular weight of less than 1,400 as crosslinking agent components (B) per 100 parts by mass of crosslinkable functional group-containing polymer (A) had good curability, peelability and contamination resistance but poor adhesion. In addition, a surface protection film using adhesive resin composition S-b4 (Comparative Example 4) for surface protection films containing 3.5 parts by mass of polyisocyanate component B-7 having a weight average molecular weight of less than 1,400 as crosslinking agent component (B) per 100 parts by mass of crosslinkable functional group-containing polymer (A) had good curability, peelability, and stain resistance, but poor adhesion and conformability to the substrate. In addition, a surface protection film using adhesive resin composition S-b2 (Comparative Example 2) for surface protection films containing 0.05 parts by mass of polyisocyanate component B-5 having a weight average molecular weight of less than 1,400 as crosslinking agent component (B) per 100 parts by mass of crosslinkable functional group-containing polymer (A) had good adhesion but poor curability, peelability, and contamination resistance. [Industrial Applicability]
[0128] According to the adhesive resin composition for surface protection films of this embodiment, it is possible to provide an adhesive resin composition for surface protection films that, when made into a surface protection film, has good application and peelability and has improved contamination caused by the adhesive during peeling.
Claims
1. A pressure-sensitive adhesive resin composition for a surface protective film, comprising a crosslinkable functional group-containing polymer (A) and a crosslinking agent component (B), The glass transition temperature Tg of the crosslinkable functional group-containing polymer (A) is −75.0° C. or more and 0.0° C. or less, The crosslinking agent component (B) contains an aliphatic or alicyclic polyisocyanate having a weight average molecular weight of 1,400 or more and 200,000 or less and an average number of isocyanate groups of 2.0 or more and 6.5 or less, the content of the crosslinking agent component (B) is 0.5 parts by mass or more and 15.0 parts by mass or less relative to 100 parts by mass of the crosslinkable functional group-containing polymer (A); The crosslinkable functional group-containing polymer (A) An acrylic polymer (A1) obtained by copolymerizing a crosslinkable functional group-containing monomer and a (meth)acrylic acid ester monomer having an ester group terminal carbon number of 1 or more and 18 or less, and having a glass transition temperature Tg of −75.0° C. or more and 0.0° C. or less, or A urethane-based polymer (A2) having a glass transition temperature Tg of −75.0° C. or more and 0.0° C. or less, the crosslinkable functional group is at least one selected from the group consisting of a hydroxyl group, an epoxy group, and a carboxy group; The adhesive resin composition for a surface protective film, wherein the aliphatic or alicyclic polyisocyanate is a polyisocyanate derived from at least one diisocyanate (b1) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a bifunctional polyol (b2) having a number average molecular weight of 1,500 or more, and a tri- or higher functional polyol (b3) having a number average molecular weight of 500 or more.
2. The adhesive resin composition for surface protective films according to claim 1, wherein the content of the structural unit derived from the crosslinkable functional group-containing monomer is 0.01 mass% or more and 25 mass% or less, based on the total mass of the crosslinkable functional group-containing polymer (A).
3. The weight average molecular weight of the crosslinkable functional group-containing polymer (A) is 2.0×10 5 Above 2.5 x 10 6 The adhesive resin composition for surface protective films according to claim 1 or 2, which is as follows:
4. The adhesive resin composition for surface protection films according to any one of claims 1 to 3, wherein the molar ratio NCO / OH of the isocyanate groups of the diisocyanate (b1) to the total molar amount of hydroxyl groups of the polyol (b2) and the polyol (b3) is 3 or more and 30 or less.
5. a mass ratio (b3) / (b2) of the polyol (b3) to the polyol (b2) is 0.1 / 99.9 or more and 99.9 / 0.1 or less; and Relative to 100 parts by mass of the diisocyanate (b1), The content of the polyol (b2) is 0.1 parts by mass or more and 250 parts by mass or less, The adhesive resin composition for surface protective films according to claim 4, wherein the content of the polyol (b3) is from 0.1 parts by mass to 190 parts by mass.
6. The adhesive resin composition for surface protective films according to claim 4 or 5, wherein the polyol (b2) and the polyol (b3) are one or more polyols selected from the group consisting of polyester polyols, polyether polyols, epoxy polyols, polyolefin polyols, and polycarbonate polyols.
7. The adhesive resin composition for surface protective films according to any one of claims 1 to 6, wherein the crosslinking agent component (B) has an isocyanate group content of 1% by mass or more and 10% by mass or less.
8. The adhesive resin composition for surface protective films according to any one of claims 1 to 7, wherein the crosslinking agent component (B) is applied onto glass, and the cured film having a thickness of 50 µm is formed after storage for 168 hours under a 23°C and 65% humidity environment, and the Konig hardness under a 23°C environment is 60 times or less.
9. A plastic film, An adhesive layer is provided on one or both sides of the plastic film, A surface protective film, wherein the adhesive layer is made of a cured product of the adhesive resin composition for surface protective films according to any one of claims 1 to 8.
10. The surface protective film according to claim 9 , wherein the adhesive layer has a thickness of 1 μm or more and 1000 μm or less.
11. The adhesive resin composition for surface protection films is applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 135° C. for 3 minutes to harden, and then stored in a 23° C., 50% RH environment for 7 days. The adhesive layer obtained by peeling the release-treated polyethylene terephthalate film from a surface protection film having an adhesive layer of 20 μm in thickness is stored in a 23° C., 50% RH environment for 7 days, wrapped in a mesh sheet, immersed in ethyl acetate at 23° C. for 1 week, removed, and dried at 120° C. for 2 hours. The gel fraction calculated by the above is 90.0 mass% or more and 100.0 mass% or less.
12. The adhesive resin composition for surface protection films was applied onto a 38 μm-thick release-treated polyethylene terephthalate film, dried at 135° C. for 3 minutes to cure, and then stored in a 23° C., 50% RH environment for 7 days. The release-treated polyethylene terephthalate film was peeled off from the surface protection film having a 20 μm-thick adhesive layer, and the adhesive layer was laminated to a thickness of 200 μm. The adhesive layer was then cut to a width of 10 mm and a length of 40 mm. The laminated adhesive layer was set in a tensile tester with a chuck distance of 10 mm, and a Young's modulus of 0.01 N / mm was measured in a tensile test performed at a speed of 300 mm / min in a 23° C. environment. 2 0.22N / mm or more 2 The surface protective film according to any one of claims 9 to 11, wherein:
13. The adhesive resin composition for surface protection films is applied onto a polyethylene terephthalate film having a thickness of 25 μm, dried at 135° C. for 3 minutes to be cured, and then stored in an environment of 23° C. and 50% RH for 7 days. The adhesive resin composition for surface protection films is applied onto a polyethylene terephthalate film having a thickness of 25 μm, a width of 25 mm, and a length of 100 mm ... then dried at 135° C. for 3 minutes to be cured, and the adhesive resin composition for surface protection films is stored in an environment of 23° C. and 50% RH for 7 days. The adhesive layer is then laminated onto a glass substrate, and the adhesive layer is pressed back and forth once with a 2 kg roller. The adhesive layer is then aged at 23° C. for 30 minutes. The 180-degree peel adhesive strength measured at 23° C. and a speed of 300 mm / min is 0.02 N / 25 mm or more and 2.50 N / 25 mm or less.
Citation Information
Patent Citations
Self-adhesive composition, self-adhesive sheet obtained by using the same and self-adhesive optical member
JP2001335767A
Adhesive composition for pasting on skin and adhesive sheet for pasting on skin
JP2006213603A
Self-adhesive composition
JP2009242725A
Self-adhesive composition, self-adhesive sheets and surface protective film
JP2010189656A
Adhesive composition and optical member surface protective film
JP2017128636A